Additive Manufacturing Solutions - Kumar, Sanjay; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book serves as an accelerated learning tool for students of Additive Manufacturing. The author presents key aspects of the subject in the form of questions and answers, so learners in a variety of contexts can find answers quickly to their specific question. Solutions to a variety of current, challenging problems are presented, clarified with examples, illustrations and copious references for more thorough investigation of the specific topic. Offers a unique, accelerated learning tool for students of Additive Manufacturing, presenting the subject in the form of questions and answers; Provides solutions to today$1 (Bs challenging problems in additive manufacturing, using examples, illustrations and references; Includes coverage of various aspects of additive manufacturing, such as materials, design, applications, post-process and digital manufacturing.s
1. Synonym -- 2. Advantage -- 3. Disadvantage -- 4. Role of Post-process -- 5. Comparison -- 6. Application -- 7. Fabrication Strategy -- 8. Mass production -- 9. Future.
Keywords: Engineering design; Production engineering; Engineering Design; Mechanical Process Engineering; Process Engineering; Additive manufacturing